Desarrollo motor en dos muestras de infantes de dos años de una institución educativa inicial privada y una institución educativa inicial estatal: una comparación entre un Programa de Desarrollo Multidimensional y un Programa Curricular Estándar - Zegarra Welsch, Evelyn (2014)
The author studies the motor development and its fine and gross motor skills components, from a quantitative approach. Research of comparative descriptive type and non-experimental design. Two samples were analyzed comparatively of a total of 76 children from two Educational Institutions of preschool level: the first of Public management and the second Private management; in which were applied two programs: the first standard and the second of Multidimensional Development. A Verification Scale of Motor Development 2 was used - VSMD - 2, which presented acceptable validity and reliability. The results revealed the existence of significant differences between both samples in global motor development and in gross motor skills; however, according to fine motor skill there is no such differences statistically corroborated. On the other hand, 15% of Private management sample showed the achievement level in motor development.